Study on Several Genus of The Solanaceae Family with Phenetic Approach Methods - hamidah, hamidah; Junairiah, Junairiah; Iftitah, Daulah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aimed to determine the morphological diversity of several genera from the Solanaceae family through a morphological approach, and the morphological characters that influence their grouping. The sampling activity is located in Lumajang district. The plant parts studied consisted of 30 characters including stature, stems, leaves and flowers which were then analyzed descriptively and phenetically. Based on the results of the descriptive analysis, it was found that there was a diversity of morphological characteristics between several genera of the Solanaceae family, namely the Solanum, Capsicum, Physalis, Datura, Nicotiana, and Petunia genera. Based on the analysis used the phenetic method in the SPSS program, a dendrogram was produced showing two groups, namely the genus Nicotiana and Petunia and the other groups Solanum, Capsicum, Datura, and Physalis. Then it grouped again and separated and finally got the species. Based on the results of PCA (Principal Component Analysis), the characters that influence the grouping of several genera from the Solanaceae family include phyllotaxis characters, leaf margins, leaf width, leaf length, leaf texture, anther color, and flower type. The result implications a morphological character can be used for plant identification.